2013
DOI: 10.1007/s12603-012-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, lifestyles, physical performance and cognitive decline: The “Treviso Longeva (Trelong)” study

Abstract: Age and higher baseline BMI, independent of gender, and other confounding factors, are risk factors for cognitive decline. Reading habit plays a protective role seven years later among northern Italian adults aged 70 years or older. Low physical performance tends, though weakly, to be associated with greater cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 92 publications
2
48
0
2
Order By: Relevance
“…Nine of the 34 articles examined the association between HGS at baseline and cognition at follow up . The follow‐up periods ranged from 3.6 to 7 years .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine of the 34 articles examined the association between HGS at baseline and cognition at follow up . The follow‐up periods ranged from 3.6 to 7 years .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used a Jamar Hand Dynamometer (n = 14). 23,26,28,30,[32][33][34]36,38,41,43,49,64,69 Other dynamometers used were from Smedley (n = 2), 62,68 Takai (n = 2), 48,61 Bruel-Kjaer (n = 1), 67 Chatillon 100 (n = 1), 66 Creative Health Products (n = 1), 65 Collins (n = 1), 29 Lafayette (n = 1), 60 Martin (n = 1), 44 Nicholas (n = 1), 40 Rolyan (n = 1) 37 and eight articles 31,35,39,42,[45][46][47]63 did not mention which dynamometer was used. The hand that was used to measure HGS varied as well.…”
Section: Selection and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Handgrip strength is a reliable surrogate for whole-body muscle strength [15], including of the lower extremities [16], and previous studies have reported that decreases in handgrip strength are associated with increased mortality [17], mobility declines [18], functional disability [19], and cognitive deterioration [20] in the elderly.…”
Section: Introductionmentioning
confidence: 99%